Absorption capacity of Structural Funds in Romania - Popa, Florina (Studies and Scientific Researches. Economics Edition, 2010)
The ability to finance and absorb more efficiently Eropean Union Funds has an important role in the process of real convergence of Romania, reported to the European Union, and recovery of gaps to other Member States. The study reveals both the essential elements of the absorption capacity and cofinancing, as well as the challenges related to structural funds absortion. Finally, we try a case study on Romania, with regard to the degree of European Funds absorption, made on the basis of statistics, in development (2007-2011).